The ability of beetles to accumulate and transfer dissociative forms of Mycobacterium bovis - Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; Zazharskyi, V. V.; Zazharsky, V. V.; Зажарський, Володимир Володимирович; Alifonova, K.; et al. (Дніпровський ДАЕУ, 2023)
The issue of tuberculosis has persisted for many years due to the active spread of the infectious agent. In Ukraine, this problem has become more acute amidst hostilities, leading to increased migration of animals, both natural and artificial. This situation poses a potential threat, exacerbating the epizootic situation and activating the spread of zoonoses. Despite this, comprehensive data on all possible sources of the pathogen and ways of introducing it to previously safe areas are still lacking. Bacteriological (microscopy, isolation of mycobacterial cultures) and analytical methods were used to identify the insects as a mechanical vector of M. bovis. To achieve this goal, the dissociative strain of M. bovis 117-a passage and L-forms of mycobacteria were used. Wheat grain was contaminated with a suspension of mycobacteria at a concentration of 10 mg of mycobacterial mass in 1cm3 of isotonic 0.9% sodium chloride solution for every 10 g of substrate. Insects were introduced into the contaminated grain, and on the 4th and 8th days, beetles were randomly selected and transferred to test tubes containing Mordovsky nutrient medium (pH 6.5) The tubes were then cultivated at a temperature of 3.0 ± 0.5°C. The study revealed the presence of experimental strains of mycobacteria in various proportions among different species of beetles. Specifically, mycobacteria were found in 100% of specimens of Oryzaephilus surinamensis, 87.5% of Calathus melanocephalus, 100% of Armadillidium vulgare, 62.5% of Rhyparochromus vulgaris, 75% of Forficula auricularia, 87.5% of Sitophilus oryzae, and 87.5% of Tenebrio molitor. This suggests that insects of different species and at different stages of development are capable of mechanically transferring mycobacteria. Additionally, the morphological similarity of microbial cells after passage through beetles with the original strain indicates that the organisms of these insects may provide a susceptible environment for mycobacteria. Проблема туберкульозу актуальна протягом багатьох років через активне поширення збудника інфекції. В Україні ця проблема загострилася в умовах бойових дій, що призвело до активізації міграції тварин, як природної, так і штучної. Така ситуація становить потенційну загрозу, загострюючи епізоотичну ситуацію та активізуючи поширення зоонозів. Незважаючи на це, досі відсутні вичерпні дані про всі можливі джерела збудника та шляхи його занесення до безпечних раніше територій. Для ідентифікації комах як механічного переносника M. bovis використовували бактеріологічні (мікроскопія, виділення культур мікобактерій) та аналітичні методи. Для досягнення поставленої мети використовували дисоціативний штам пасажу M. bovis 117-a та L-форми мікобактерій. Зерно пшениці контамінували суспензією мікобактерій у концентрації 10 мг маси мікобактерій в 1 см3 ізотонічного 0,9 % розчину натрію хлориду на кожні 10 г субстрату. У заражене зерно вносили комах, а на 4-8 добу випадковим чином відбирали жуків і переносили в пробірки з живильним середовищем Мордовського (рН 6,5). Потім пробірки культивували при температурі 3,0 ± 0,5°С. Дослідження виявило наявність експериментальних штамів мікобактерій у різних пропорціях серед різних видів жуків. Зокрема, мікобактерії були виявлені у 100% зразків Oryzaephilus surinamensis, 87,5% Calathus melanocephalus, 100% Armadillidium vulgare, 62,5% Rhyparochromus vulgaris, 75% Forficula auricularia, 87,5% Sitophilus oryzae та 87,5% Tenebrio molitor . Це свідчить про те, що комахи різних видів і на різних стадіях розвитку здатні до механічного перенесення мікобактерій. Крім того, морфологічна схожість мікробних клітин після проходження через жуків з вихідним штамом вказує на те, що організми цих комах можуть забезпечувати чутливе середовище для мікобактерій.
Здатність жуків до накопичення та перенесення дисоціативних форм Mycobacterium bovis
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Аліфонова Кіра Володимирівна https://orcid.org/0000-0002-0767-5305 Козак Наталія Ігорівна https://orcid.org/0000-0001-6672-4085 Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X
Keywords: Mycobacterium; мікобактерія; insects; комахи; microscopy; мікроскопія